Neuroprotective effect of Vinpocetine against 3- NP Induced reduction of body weight and oxidative stress in Rats - Meenakshi Ratra; PL Sharma; Rajesh Gupta (International Journal of Phytomedicine, 2011)
Huntington’s disease is a progressive, degenerative disease characterized by abnormal body movements symptoms like chorea and a reduction of body weight. Recently, it has been reported that oxidative stress, which is one of the pathological hallmarks of various neurodegenerative disorders, also plays an important role in the pathogenesis of Huntington’s disease. 3- Nitropropionic acid, a neurotoxin treatment significantly reduction in body weight. Intraperitoneal administration of 3-nitropropionic acid (10 mg/kg for 14 days) caused significant loss of body weight and poor rentention of memory. Biochemical analysis revealed that 3-NP administration significantly increase in lipid peroxidation in the brains of rats. The present study demonstrated that inhibition of type 1 phosphodiesterase (PDE1) by vinpocetine (5, 10 & 20mg) significantly reversed behavioral and biochemical dysfunction in 3-NP treated group. The result of the present study suggests facilitatory role of PDE1 enzyme in loss in body weight and oxidative stress following 3-NP injection.